Analysis of students' mathematics communication ability based on cognitive styles and mathematical knowledge - Syahrul Azmi; Baidowi Baidowi; Nurul Hikmah; Ratna Yulis Tyaningsih; Eka Kurniawan (Jurnal Pijar Mipa, 2022)
This study aims to describe the mathematical communication skills of mathematics education students based on their cognitive styles and mathematical knowledge. This research is a qualitative approach. Data were collected by giving the MFFT test to the students to measure their cognitive styles and essay tests for determining their mathematical communication skills. Data were analyzed by comparing the scores of cognitive styles, mathematical communication, and their mathematical performances. The result shows that students with reflective cognitive styles perform better on mathematical communication than impulsive cognitive styles. Moreover, their mathematical knowledge significantly affects their abilities in solving mathematical communication tests.